Evolução da concentração e da inovação na indústria de transformação brasileira entre 1998 e 2011 - Padilha, Ícaro Fernando da Silva (2016)
This dissertation analyzes the relationship between concentration and innovation in the Brazilian industry between 1998 and 2011. It uses the econometric treatment on a database involving 17 industries in 5 periods. Based on previous studies, we seek to understand if this relationship is expressed as a behavior of inverted-U curve. Such behavior says that for low levels of industrial concentration, there is a direct relationship between concentration and innovation. On the other hand, from a certain level, there is an inverse relationship between concentration and innovation. The addition of variables related to technological opportunity allow the finding of statistical significance of other factors that also contribute to the determination of innovative capacity, as public financing of R&D.